Historical aspects of printing and publishing in languages of the Middle East : papers from the Third Symposium on the History of Printing and Publishing in the Languages and Countries of the Middle East, University of Leipzig, September 2008 - Roper, Geoffrey. (Islamic Manuscripts and Books, 2013)
Print culture, in both its material and cognitive aspects, has been a somewhat neglected field of Middle Eastern intellectual and social history. The essays in this volume aim to make significant contributions to remedying this neglect, by advancing our knowledge and understanding of how and why the development of printing both affected, and was affected by, historical, social and intellectual currents in the areas considered. These range geographically from Iran to Latin America, via Kurdistan, Turkey, Egypt, the Maghrib and Germany, temporally from the 10th to the 20th centuries CE, and linguistically through Arabic, Judæo-Arabic, Syriac, Ottoman Turkish, Kurdish and Persian.